Promoting competition in the port sector: an analysis from the global models and application to the Brazilian case - Britto, Paulo Augusto P. de (2015)
The growth in demand for services in the infrastructure sectors, coupled with the lack of public investment, led to policies to promote private participation in those sectors. In the port sector, the private participation started in the early 90s, when the growth of international trade resulted from increasing globalization has highlighted the generalized inefficiency of this sector. This article aims to discuss the private participation in the port sector from the analysis of ways of organization, as well as the evolution of this sector in different countries, analyzing the possible competition models associated to different ownership structures in the areas of the port. The article also presents the evolution and the current organization of the Brazilian port model. Throughout the discussion, examples of ports are presented to illustrate the discussed concepts.